EVALUASI PENGAKUAN, PENGUKURAN, PENCATATAN DAN PELAPORAN AKTIVA TETAP MENURUT PP NO. 71 TAHUN 2010 PADA DINAS KOPERASI DAN UMKM PROVINSI SULAWESI UTARA - Najoan, Getruida Neni Revina; Tinangon, Jantje J.; Walandouw, Stanley Kho (Universitas Sam Ratulangi, 2018)
Fixed assets have significant contributions to governance. In the government's balance sheet, the fixed assets account is a significant and material account. fixed assets are considered important to support the implementation of government functions in terms of service to the community. Therefore, accounting treatment in the case of recognition, measurement, recording and reporting of fixed assets must comply with SAP. The purpose of this study is to evaluate whether the recognition, measurement, recording and reporting of fixed assets at the Department of Cooperatives and SMEs North Sulawesi Province is in accordance with Government Regulation No. 71 of 2010. Research Methods used are descriptive whose purpose each data collected analyzed then drawn conclusions and the type of research used is qualitative descriptive. The results showed that the recognition, measurement, recording and reporting of fixed assets Department of Cooperatives and SMEs North Sulawesi Province has been in accordance with Government Regulation No. 71 of 2010.Keywords: Recognition, Measurement, Recording and Reporting, Fixed Assets, Governmental Accounting Standards